2017
DOI: 10.1016/j.jclepro.2017.04.096
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of energy demand from computer numerical control (CNC) toolpaths

Abstract: It is important to accurately model the total electrical energy requirements in order to compare and select the least energy consumption toolpath in a manufacturing process. To enable this goal in this study, a feed axes energy demand model (which incorporates the weights of feed axes, machine vice, and workpiece) proposed in previous work by the authors was integrated and used to refine the energy consumption models for machine tools to analytically estimate the power and processing time, and hence energy req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The measurements for surface roughness, Ra (µm), at the base (B) and walls (W) of the molds and the EEC (kJ) [21,24] corresponding to each of the 32 tests undertaken are shown in Table 3. This table also shows the active electrical energy consumed by the machining center during each cycle of milling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements for surface roughness, Ra (µm), at the base (B) and walls (W) of the molds and the EEC (kJ) [21,24] corresponding to each of the 32 tests undertaken are shown in Table 3. This table also shows the active electrical energy consumed by the machining center during each cycle of milling.…”
Section: Resultsmentioning
confidence: 99%
“…Priarone [20] has evaluated the electrical consumption of a shaping grinding process for different process parameters via a full factorial experimental plan. Eden and Mativenga [21] have quantified the electrical consumption of a milling machine for different linear paths (G1) and circular paths (G2 and G3) in order to predict the electric demand of the machine during the execution of a NC program. Guerra-Zubiaga et al [22] have studied different cutting trajectories and cutting parameters (feed rate, spindle speed, and depth of cut) in a slot milling process to analyze its influence on electrical consumption of the machining center.…”
Section: Introductionmentioning
confidence: 99%
“…The Graphic User Interface (GUI), inspired by Edem and Mativenga's work [9], as seen in Fig. 3, is developed to assist the estimation of the energy consumption.…”
Section: The First Paragraph Third Sentence Of the Section 22 Modelling Energy Estimation Of Axis Feed Should Be Replaced As Followsmentioning
confidence: 99%
“…Energy consumption on the spindle motor and each axis feed motor is then processed using a Graphical User Interface, by computing the energy consumption as a summation of the energy on all the lines of the NC code. Previously, other researchers have developed energy model and energy prediction software to analytically estimate the power consumption and the processing time [9]. This research was used to develop an NC code-based software to predict the lowest energy consumption in machining a certain workpiece.…”
Section: The Last Paragraph On the 1 Introduction Section Should Be Replaced As Followsmentioning
confidence: 99%
“…Edem and Mativenga [11] focused on an improved prediction model of energy requirements by incorporating weight factor of feed drive. In their work, it is concluded that toolpath with longer linear path segments should be selected to reduce energy demand in machining.…”
Section: Introductionmentioning
confidence: 99%